Murraya koenigii Extract Loaded Phytosomes Prepared using Antisolvent Precipitation Technique for Improved Antidiabetic and Hypolidemic Activity - Rani, Anjna; Kumar, Sunil; Khar, Roop K (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Phytosome is a novel technique introduced by Indena that combines standardised herbal extract and phospholipid in preferably equal ratio to provide better absorption enhancing bioavailability. Purpose: The objective of proposed study is to prepare, optimise and characterize phytosomes of Murraya koenigii (Linn.) Spreng extract to improve its antidiabetic properties. Materials and Methods: Antisolvent precipitation technique was used to prepare phytosomes. Design expert software was used to evaluate the impact of soya lecithin and cholesterol concentration on various dependent variables such as particle size, span value and entrapment efficiency. Streptozotocin-nicotinamide induced diabetes model was used to evaluate in vivo antidiabetic activity in rats for extract as well as prepared phytosomes. Results: The phytosomes were successfully designed and optimised for particle size, entrapment efficiency, span value, and zeta potential of 236 nm, 75.1%, 0.395 and -16.85 mV respectively. Streptozotocinnicotinamide induced diabetes model was used to study antidiabetic potential of plant extracts and its optimized phytosomal formulations in male Wistar rats. Optimized phytosomal formulation showed significant reduction in serum glucose concentration at lower dose, suggesting enhancement in its therapeutic efficacy. Conclusion: We were successful in formulation, optimization and characterization of phytosomes for Murraya koenigii extract. The tested phytosomes showed better antidiabetic and hypolipidemic activities as compared to crude extract in male Wistar rats.
Keywords: Murraya koenigii; Phytosomes; Antidiabetics; Herbal formulation; Herbal; extract